Leakage current and structural analysis of annealed HfO2/La2O3 and CeO2/La2O3 dielectric stacks : a nanoscopic study - Shubhakar, Kalya (2014)
Grain boundaries in the polycrystalline microstructure of post-annealed high-κ (HK) dielectrics are a major limitation in the reliability of HK dielectrics used for advanced CMOS technologies. Another challenge in the field of HK dielectrics is to ensure higher drain drive current in CMOS, while maintaining low leakage current. In this work, the authors demonstrate enhanced performance of HfO2 and CeO2 dielectrics by incorporating lanthanum. The resulting stacks show promising dielectric characteristics with reduced leakage current and uniform (amorphous) crystal structure. The improved HK characteristics were shown to occur even over nanometer-length scales using scanning probe microscopy and transmission electron microscopy, in agreement with previous studies based on micron-scale device-level measurement.